1997
DOI: 10.1177/112067219700700205
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Surgery in Fuchs’ Heterochromic Iridocyclitis

Abstract: Extracapsular cataract extraction in patients with Fuchs' heterochromic iridocyclitis does not currently present any difficulties compared with normal senile cataract. No major complications occurred and the final visual acuity was satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Others have reported VA of 20/40 or better in 76% to 89% of patients with ECCE and a PC IOL. 19,23,25,28,32 Vitreous haze is the most common cause of postoperative visual impairment in FHIC and has been reported in 12% to 50% of cases. [24][25][26] In our study, 16 eyes (39%) had mild to moderate vitreous haze, which was the main cause of VA less than 20/20 in 13 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported VA of 20/40 or better in 76% to 89% of patients with ECCE and a PC IOL. 19,23,25,28,32 Vitreous haze is the most common cause of postoperative visual impairment in FHIC and has been reported in 12% to 50% of cases. [24][25][26] In our study, 16 eyes (39%) had mild to moderate vitreous haze, which was the main cause of VA less than 20/20 in 13 patients.…”
Section: Discussionmentioning
confidence: 99%
“…26,[32][33][34] It is more common in patients with PMMA IOLs than in those with acrylic IOLs. 10,11 Hydrophilic acrylic IOLs have been successfully implanted in uveitis patients 12 ; however, AbelaFormanek et al 29 concluded that despite the better uveal biocompatibilty of the hydrophilic acrylic IOLs, they should not be recommended for cataract surgery in uveitic eyes because of early and accelerated development of PCO.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of PCO in FHI varies from 20 % to 45 % (Sherwood et al, 1992), (Avramides et al, 1997) and (Guzak et al, 1987). Bhargava et al, 2013, report an incidence of 16.7 % following manual SICS in patients with uveitis.…”
Section: Complicationsmentioning
confidence: 99%
“…The rate of PCO in FHU patients has been reported to be 20%-45% (Figure 4) [20][21][22]. Javadi et al [8] did not detect clinically significant PCO in eyes with acrylic IOLs.…”
Section: Discussionmentioning
confidence: 99%